The Cambridge companion to comparative constitutional law - Masterman, Roger; Schütze, Robert (Cambridge companions to law, 2019)
"What is the purpose of comparative constitutional law? Comparing constitutions allows us to consider the similarities and differences in forms of government, and the normative philosophies behind constitutional choices. Constitutional comparisons offer "hermeneutic" help: they enable us to see "our" own constitution with different eyes and to locate its structural and normative choices by references to alternatives evident in other constitutional orders"--